2018
DOI: 10.1016/j.celrep.2018.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Enhancer Activation by Pharmacologic Displacement of LSD1 from GFI1 Induces Differentiation in Acute Myeloid Leukemia

Abstract: SummaryPharmacologic inhibition of LSD1 promotes blast cell differentiation in acute myeloid leukemia (AML) with MLL translocations. The assumption has been that differentiation is induced through blockade of LSD1’s histone demethylase activity. However, we observed that rapid, extensive, drug-induced changes in transcription occurred without genome-wide accumulation of the histone modifications targeted for demethylation by LSD1 at sites of LSD1 binding and that a demethylase-defective mutant rescued LSD1 kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
201
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(229 citation statements)
references
References 48 publications
25
201
3
Order By: Relevance
“…3a). Importantly, we found that LSD1i treatment of MCC leads to dissociation of this complex, which is in line with studies in leukemias 16,17 (Fig. 3d,e).…”
Section: And Extended Datasupporting
confidence: 92%
“…3a). Importantly, we found that LSD1i treatment of MCC leads to dissociation of this complex, which is in line with studies in leukemias 16,17 (Fig. 3d,e).…”
Section: And Extended Datasupporting
confidence: 92%
“…Global or promoter‐specific accumulation of methylation of H3K4 is not always seen following KDM1A inhibition regardless of decreased KDM1A activity . However, in our findings, the global change in H3K4me2 upon treatment with all KDM1A inhibitors demonstrated capacity to effectively inhibit KDM1A catalytic activity.…”
Section: Discussionmentioning
confidence: 67%
“…is not always seen following KDM1A inhibition regardless of decreased KDM1A activity. 23,34 However, in our findings, the global change in with the clinical candidate compounds and has the same mechanism of action through irreversible covalent modification of the FAD cofactor, also had no effect on the cell viability of Ewing sarcoma cells in 2D and 3D. Prolonged inhibition, as a means to achieve maximal efficacy, as in reports with inhibitors of Enhancer of Zeste Homolg 2 (EZH2) in lymphoma, did not alter the response to these inhibitors of KDM1A catalytic function.…”
Section: Global or Promoter-specific Accumulation Of Methylation Of H3k4mentioning
confidence: 99%
“…Furthermore, the H3K4me1 histone mark regulated by LSD1 was seen to be enriched in intergenic regions of pHGG cells 9 , suggesting that LSD1 may control access to enhancers of genes important in pHGG pathology. LSD1 inhibitors can functionally target either the catalytic domain that mediates demethylation 17 , or the scaffolding tower domain that interfaces with other proteins in epigenetic complexes 18 , and it is currently unknown what phenotype these disparate inhibitors would produce in pHGG. Given the highly disrupted yet therapeutically sensitive epigenome of pHGGs, we sought to explore in this study whether LSD1 inhibition could be both cytotoxic to pHGG and generate transcriptional changes that would inform combination therapies.…”
Section: Introductionmentioning
confidence: 99%